Heat shock protein: a double-edged sword linking innate immunity and hepatitis B virus infection - Wen-ying Dai; Guo-qing Yao; Xi-chuan Deng; Guang-chao Zang; Jia Liu; Guang-yuan Zhang; Yu-meng Chen; Ming-qi Lv; Ting-ting Chen (Elsevier, 2023)
Heat shock proteins (HSPs), which have a variety of functions, are one of the stress protein families. In recent years, They have been reported to play a dual role in hepatitis B virus (HBV) which as persistent infection which is associated with, cirrhosis and liver cancer. In this article, we have summarized the regulatory mechanisms between HSPs and viruses, especially HBV and associated diseases based on HSP biological functions of in response to viral infections. In view of their potential as broad-spectrum antiviral targets, we have also discuss current progress and challenges in drug development based on HSPs, as well as the potential applications of agents that have been evaluated clinically in HBV treatment.